Method for in-situ synthesis of low-radiation-absorption-ratio white oxide ceramic coating on surface of magnesium-lithium alloy

The zirconium salt-zinc salt system electrolyte is used to perform microarc oxidation on the surface of magnesium lithium alloy, and a low-spray-absorbing white oxide ceramic coating is prepared, which solves the problem of poor thermal control performance of the existing coating and achieves high binding Power and excellent thermal control performance, suitable for spacecraft applications.

CN119265668APending Publication Date: 2025-01-07NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411695416.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing surface coatings of magnesium lithium alloys have poor thermal control performance in high temperature environments, especially the solar absorption rate of black oxide coatings is too high, resulting in poor thermal control performance and poor binding force with magnesium alloy substrate, which is difficult to meet. High performance requirements for spacecraft.

Method used

The microarc oxidation process is carried out by using the zirconium salt-zinc salt system electrolyte to synthesize a low-spoke white oxide ceramic coating on the surface of magnesium lithium alloy in situ. Through electrochemical reactions, the composition, pore size distribution and surface of the coating are controlled. Roughness, achieving high binding force and excellent thermal control performance.

Benefits of technology

The preparation of a white oxide ceramic coating with low radiation absorption ratio on the surface of magnesium lithium alloy is achieved, which reduces the solar absorption rate and increases the infrared emissivity. The infrared emissivity of the coating can reach up to 0.84 and the solar absorption rate can reach up to 0.35. Suitable for thermal control needs in the aerospace field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265668A_ABST
    Figure CN119265668A_ABST
Patent Text Reader

Abstract

The invention discloses a method for in-situ synthesis of a low-radiation-absorption-ratio white oxide ceramic coating on the surface of a magnesium-lithium alloy, which comprises the following steps: clamping a pretreated LA103Z magnesium-lithium alloy by using a hanger, placing the LA103Z magnesium-lithium alloy in an electrolytic bath, completely immersing the LA103Z magnesium-lithium alloy in an electrolyte and taking the LA103Z magnesium-lithium alloy as an anode, and taking a stainless steel sheet as a cathode; a power source is set to be in a constant-voltage segmented working mode for micro-arc oxidation treatment, and a low-radiation-absorption-ratio white oxide ceramic coating is synthesized on the surface of the LA103Z magnesium-lithium alloy in situ; the electrolyte is a zircon salt-zinc salt system solution. According to the method, the zirconium salt-zinc salt system electrolyte is adopted to perform micro-arc oxidation process to synthesize the white oxide ceramic coating on the surface of the magnesium-lithium alloy in situ, the content of Zn element in the coating is regulated by regulating the concentration of zinc salt in the electrolyte, and meanwhile, the aperture size and roughness of the coating are regulated by utilizing constant-pressure segmented regulation, so that the surface of the magnesium-lithium alloy is coated with the white oxide ceramic coating. Therefore, the infrared emissivity of the coating is improved, the solar absorptivity is reduced, the low radiation absorption ratio of the coating is achieved, and the coating is suitable for the aerospace field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium alloy surface treatment, and in particular relates to a method for in-situ synthesis of a low-radiation absorption ratio white oxide ceramic coating on the surface of a magnesium-lithium alloy. Background Art

[0002] With the development of aerospace technology, especially major aerospace projects such as manned spaceflight and lunar exploration, there is a clear and urgent demand for lightweight spacecraft. Magnesium-lithium alloys are known for their low density (density 1.35g / cm 3 ~1.65g / cm 3 ), with the advantages of high specific strength / specific stiffness, good electrical and thermal conductivity, excellent damping and vibration reduction, strong electromagnetic interference shielding and easy machining, it is widely used in structures such as spacecraft instrument housings, fastening connection components, and truss brackets. However, during the in-orbit operation, the spacecraft constantly experiences the Earth's dark side and sun-facing side, and its surface needs to withstand high and low temperature alternations of up to ±200°C in a short period of time. In addition, the internal heat source formed by the changes in the thermal power consumption of the spacecraft's instruments and equipment itself causes high temperatures and temperature gradients to form on the inner and outer surfaces of the spacecraft and the surfaces of the instruments and equipment, resulting in an increase in the heat load on the magnesium-lithium alloy structure, which seriously affects the internal thermal environment of the spacecraft and its normal in-orbit operation. Therefore, aerospace workers at home and abroad have developed a series of low radiation absorption ratio (low solar absorptivity and high infrared emissivity) thermal control coatings for thermal control.

[0003] At present, low radiation absorption ratio thermal control coatings on the surface of magnesium-lithium alloys are prepared by spraying white paint with white wide bandgap oxides (ZnO, TiO2, ZrO2) as pigments and anodic oxidation. Although white paint has excellent emissivity and is used in aerospace systems; however, white paint has poor bonding with the magnesium alloy matrix, and its performance will deteriorate after long-term service in orbit. The MgO film layer generated by anodic oxidation is loose and easy to fall off, and its own emissivity is very low, which cannot meet the high-performance thermal control requirements of spacecraft.

[0004] In recent years, with the development of technology in the aerospace field, the preparation of ceramic coatings with thermal control properties on the surface of magnesium alloys by micro-arc oxidation technology has gradually attracted the attention of researchers. However, most of the coating research in this direction focuses on black oxide coatings with high emissivity. Although the emissivity of the black coating of magnesium alloy prepared by micro-arc oxidation can reach above 0.8, the solar absorptivity of the black coating itself is mostly higher than 0.7, resulting in poor thermal control performance of the coating. Therefore, preparing a white ceramic coating with low radiation absorption ratio (low solar absorptivity and high infrared emissivity) on the surface of magnesium-lithium alloy to make it have high bonding strength will be of great significance for the large-scale application of magnesium-lithium alloys in aerospace systems. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for in-situ synthesis of a low radiation absorption ratio white oxide ceramic coating on the surface of a magnesium-lithium alloy in view of the deficiencies of the above-mentioned prior art. The method adopts a zirconium salt-zinc salt system electrolyte to carry out a micro-arc oxidation process, and synthesizes a white oxide ceramic coating in-situ on the surface of a magnesium-lithium alloy through an electrochemical reaction, while ensuring a high bonding strength between the coating and the magnesium-lithium alloy, reducing the solar absorption rate of the coating and increasing the infrared emissivity of the coating, achieving a low radiation absorption ratio of the coating, and solving the problem that the existing black oxide coating has a high solar absorption rate and leads to poor thermal control performance of the coating.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for in-situ synthesis of a low-radiation absorption ratio white oxide ceramic coating on the surface of a magnesium-lithium alloy, characterized in that the process of the method is: a LA103Z magnesium-lithium alloy pre-treated by clamping with a hanger is placed in an electrolytic cell, and is completely immersed in an electrolyte and used as an anode, a stainless steel sheet is used as a cathode, and a power supply is set to a constant voltage segmented working mode for micro-arc oxidation treatment, and a low-radiation absorption ratio white oxide ceramic coating is in-situ synthesized on the surface of the LA103Z magnesium-lithium alloy; the electrolyte is a zirconium salt-zinc salt system solution.

[0007] Usually, the pretreatment of LA103Z magnesium-lithium alloy is as follows: firstly, it is cleaned and degreased with an organic cleaning agent, and then immersed in anhydrous ethanol for standby use.

[0008] The above-mentioned method for in-situ synthesis of low-radiometric white oxide ceramic coating on the surface of magnesium-lithium alloy is characterized in that the composition of the electrolyte includes: the concentration of ammonium fluorozirconate is 6g / L, the concentration of sodium dihydrogen phosphate is 6g / L, the concentration of ammonium fluoride is 2g / L, the concentration of zinc dihydrogen phosphate is 4g / L to 16g / L, and the concentration of sodium hydroxide is 1g / L. The present invention ensures the preparation of low-radiometric white oxide ceramic coating mainly based on ZrO2-ZnO-MgO by controlling the composition of the electrolyte.

[0009] The above-mentioned method for in-situ synthesis of low-radiation absorption ratio white oxide ceramic coating on the surface of magnesium-lithium alloy is characterized in that the power supply is a constant voltage DC pulse power supply, and the process parameters of the micro-arc oxidation treatment are: termination voltage 400V, frequency 1000Hz, duty cycle 15%, oxidation time 15min. The present invention adopts a constant voltage DC pulse power supply to control the oxidation voltage in sections, thereby optimizing the coating aperture control and realizing the preparation of low-radiation absorption ratio coating.

[0010] The above-mentioned method for in-situ synthesis of low-radiation absorption ratio white oxide ceramic coating on the surface of magnesium-lithium alloy is characterized in that the voltage control mode during the micro-arc oxidation treatment is segmented control, and the segmented control process is: in the initial stage of micro-arc oxidation, the voltage is increased from 0V to 300V during the period of 0 to 1min; in the micro-arc oxidation process stage, the voltage is increased from 300V to 350V during the period of 1min to 2min; in the micro-arc oxidation process stage, the voltage is increased from 350V to 380V during the period of 2min to 5min; in the micro-arc oxidation process stage, the voltage is increased from 380V to 400V during the period of 5min to 7min; in the micro-arc oxidation constant voltage stage, the voltage is maintained at 400V during the period of 7min to 15min. The present invention ensures the pore size distribution characteristics of the coating by controlling the process parameters during the micro-arc oxidation treatment and performing segmented control of the micro-arc oxidation voltage. Specifically, the pore size of the coating is adjusted to be within the wavelength range of sunlight, so that sunlight will not be reflected after entering the micropores of the coating, thereby increasing the solar absorptivity of the coating; or the pore size of the coating is adjusted to be larger than the wavelength range of sunlight, so that sunlight will be easily reflected after entering the micropores of the coating, thereby reducing the solar absorptivity of the coating, thereby enabling the coating to have optimal thermal control performance according to the requirements of the usage scenario.

[0011] The above-mentioned method for in-situ synthesis of low-radiation absorption ratio white oxide ceramic coating on the surface of magnesium-lithium alloy is characterized in that the low-radiation absorption ratio white oxide ceramic coating is mainly composed of ZrO2-ZnO-MgO, and the pore size characteristics of the coating are: micropores with an pore size of less than 4μm account for 52% to 74%, micropores with an pore size of 4μm to 8μm account for 23% to 31%, micropores with an pore size of 8μm to 11μm account for 2% to 6%, and micropores with an pore size of 11μm to 18μm account for 1% to 11%, and the solar absorptivity of the coating is 0.35 to 0.56, the infrared emissivity of the coating is 0.79 to 0.84, and the surface roughness of the coating is Ra3.58 to Ra5.89. The ZnO in the coating itself has excellent thermal control properties, so the thermal control properties of the coating can be controlled by adjusting the ZnO content in the coating, and the solar absorptivity of the coating can be controlled by adjusting the pore size distribution, and the specific surface area of ​​the coating can be adjusted by adjusting the surface roughness of the coating, thereby adjusting the ability of the coating to radiate external energy, that is, the emissivity of the coating; in summary, the present invention achieves optimal thermal control properties by coordinated matching of the main components, pore size distribution and roughness of the white oxide ceramic coating.

[0012] Compared with the prior art, the present invention has the following advantages:

[0013] 1. The present invention adopts a zirconium salt-zinc salt system electrolyte to carry out a micro-arc oxidation process, coordinates the electrolyte system with the process, and synthesizes a white oxide ceramic coating in situ on the surface of the magnesium-lithium alloy through an electrochemical reaction. While ensuring a high bonding strength between the coating and the magnesium-lithium alloy, the coating composition, pore size distribution and roughness are coordinated and regulated, the solar absorptivity of the coating is reduced and the infrared emissivity of the coating is increased, and a low radiation absorption ratio of the coating is achieved.

[0014] 2. The micro-arc oxidation process of the present invention adopts a constant pressure segmented control method to adjust the pore size and roughness of the coating and achieve a coordinated match between the two, thereby increasing the infrared emissivity of the coating and reducing the solar absorptivity.

[0015] 3. The present invention adjusts the zinc salt concentration in the zirconium salt-zinc salt system electrolyte to regulate the in-situ synthesis of white oxide ceramic coatings mainly composed of ZrO2-ZnO-MgO with different Zn element contents, that is, the ZnO content with thermal control properties itself is adjusted to achieve the regulation of the thermal control properties of the coating.

[0016] 4. The low-radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of magnesium-lithium alloy of the present invention has an infrared emissivity of up to 0.84 and a solar absorptivity of down to 0.35. It has excellent low-radiation absorption ratio performance and is suitable for the aerospace field.

[0017] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a surface scanning electron microscope image of a low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of a LA103Z magnesium-lithium alloy sheet in Example 1 of the present invention.

[0019] Figure 2 This is a graph showing the pore size distribution results of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in Example 1 of the present invention.

[0020] Figure 3 This is a cross-sectional scanning electron microscope image of a white oxide ceramic coating with low radiation absorption ratio synthesized in situ on the surface of a LA103Z magnesium-lithium alloy sheet in Example 1 of the present invention.

[0021] Figure 4 This is an O1s binding energy diagram of the XPS analysis of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in Example 1 of the present invention.

[0022] Figure 5 This is a surface scanning electron microscope image of a low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of a LA103Z magnesium-lithium alloy sheet in Example 2 of the present invention.

[0023] Figure 6 This is a graph showing the pore size distribution results of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in Example 2 of the present invention.

[0024] Figure 7 This is a cross-sectional scanning electron microscope image of a white oxide ceramic coating with low radiation absorption ratio synthesized in situ on the surface of a LA103Z magnesium-lithium alloy sheet in Example 2 of the present invention.

[0025] Figure 8 This is an O1s binding energy diagram of the XPS analysis of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in Example 2 of the present invention. DETAILED DESCRIPTION

[0026] Example 1

[0027] This embodiment includes the following steps:

[0028] Step 1: After grinding the LA103Z magnesium-lithium alloy sheet with a size (length × width × thickness) of 15 mm × 15 mm × 3 mm, ultrasonically degrease the sheet in an organic cleaning agent at room temperature for 5 min, and then immerse the sheet in anhydrous ethanol for standby use, thereby completing the pretreatment;

[0029] Step 2: Add zirconate, zinc salt and auxiliary salt to deionized water in sequence to prepare an electrolyte for coating preparation; the electrolyte comprises: ammonium fluorozirconate at a concentration of 6 g / L, sodium dihydrogen phosphate at a concentration of 6 g / L, ammonium fluoride at a concentration of 2 g / L, zinc dihydrogen phosphate at a concentration of 4 g / L, and sodium hydroxide at a concentration of 1 g / L;

[0030] Step 3: Use a hanger to clamp the LA103Z magnesium-lithium alloy sheet pretreated in step 1 and place it in an electrolytic cell containing the electrolyte prepared in step 2, so that the pretreated LA103Z magnesium-lithium alloy sheet is completely immersed in the electrolyte and serves as an anode, and a stainless steel sheet is used as a cathode, and the power supply is set to a constant voltage DC pulse power supply mode for micro-arc oxidation treatment, and a low radiation absorption ratio white oxide ceramic coating is in situ synthesized on the surface of the LA103Z magnesium-lithium alloy sheet;

[0031] The process parameters of the micro-arc oxidation treatment are: a termination voltage of 400V, a frequency of 1000Hz, a duty cycle of 15%, and an oxidation time of 15min. The voltage control method during the micro-arc oxidation treatment is segmented control, and the segmented control process is: in the initial stage of micro-arc oxidation, during a period of 0 to 1min, the voltage is increased from 0V to 300V; in the period of 1min to 2min during the micro-arc oxidation process, the voltage is increased from 300V to 350V; in the period of 2min to 5min during the micro-arc oxidation process, the voltage is increased from 350V to 380V; in the period of 5min to 7min during the micro-arc oxidation process, the voltage is increased from 380V to 400V; in the period of 7min to 15min during the constant voltage stage of micro-arc oxidation, the voltage is maintained at 400V.

[0032] The low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment was subjected to energy spectrum EDS analysis, and the results are shown in Table 1 below.

[0033] Table 1

[0034] element Mg Zr Zn O F Total Mass ratio (%) 20.94 41.70 6.14 27.55 3.67 100

[0035] As can be seen from Table 1, the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment is composed of elements such as Mg, Zr, Zn, O, and F.

[0036] The infrared emissivity, solar absorptivity and roughness tests were performed on the low-radiation absorption ratio white oxide ceramic coating in situ synthesized on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment. The test results showed that the infrared emissivity of the coating was 0.79, the solar absorptivity was 0.56, and the surface roughness was Ra3.58.

[0037] Figure 1 The surface scanning electron microscope image of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment is shown in FIG. Figure 1 It can be seen that the micropores of the coating have various sizes, which helps to adjust the thermal control performance of the coating.

[0038] Figure 2 The pore size distribution result of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment is shown in FIG. Figure 2 It can be seen that the pore size characteristics of the coating are: micropores with a pore size of less than 4μm account for 74%, micropores with a pore size of 4μm to 8μm account for 23%, micropores with a pore size of 8μm to 11μm account for 2%, and micropores with a pore size of 11μm to 18μm account for 1%.

[0039] Figure 3The cross-sectional scanning electron microscope image of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment is shown in FIG. Figure 3 It can be seen that the low radiation absorption ratio white oxide ceramic coating is tightly bonded to the LA103Z magnesium-lithium alloy substrate, indicating that the coating has excellent bonding strength.

[0040] Figure 4 The O1s binding energy diagram of the XPS analysis of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment is shown in FIG. Figure 3 It can be seen that the main phases of the low radiation absorption ratio white oxide ceramic coating are ZrO2, ZnO and MgO.

[0041] Example 2

[0042] This embodiment includes the following steps:

[0043] Step 1: After grinding the LA103Z magnesium-lithium alloy sheet with a size (length × width × thickness) of 15 mm × 15 mm × 3 mm, ultrasonically degrease the sheet in an organic cleaning agent at room temperature for 5 min, and then immerse the sheet in anhydrous ethanol for standby use, thereby completing the pretreatment;

[0044] Step 2: Add zirconate, zinc salt and auxiliary salt to deionized water in sequence to prepare an electrolyte for coating preparation; the electrolyte comprises: ammonium fluorozirconate at a concentration of 6 g / L, sodium dihydrogen phosphate at a concentration of 6 g / L, ammonium fluoride at a concentration of 2 g / L, zinc dihydrogen phosphate at a concentration of 16 g / L, and sodium hydroxide at a concentration of 1 g / L;

[0045] Step 3: Use a hanger to clamp the LA103Z magnesium-lithium alloy sheet pretreated in step 1 and place it in an electrolytic cell containing the electrolyte prepared in step 2, so that the pretreated LA103Z magnesium-lithium alloy sheet is completely immersed in the electrolyte and serves as an anode, and a stainless steel sheet is used as a cathode, and the power supply is set to a constant voltage DC pulse power supply mode for micro-arc oxidation treatment, and a low radiation absorption ratio white oxide ceramic coating is in situ synthesized on the surface of the LA103Z magnesium-lithium alloy sheet;

[0046] The process parameters of the micro-arc oxidation treatment are: a termination voltage of 400V, a frequency of 1000Hz, a duty cycle of 15%, and an oxidation time of 15min. The voltage control method during the micro-arc oxidation treatment is segmented control, and the segmented control process is: in the initial stage of micro-arc oxidation, during a period of 0 to 1min, the voltage is increased from 0V to 300V; in the period of 1min to 2min during the micro-arc oxidation process, the voltage is increased from 300V to 350V; in the period of 2min to 5min during the micro-arc oxidation process, the voltage is increased from 350V to 380V; in the period of 5min to 7min during the micro-arc oxidation process, the voltage is increased from 380V to 400V; in the period of 7min to 15min during the constant voltage stage of micro-arc oxidation, the voltage is maintained at 400V.

[0047] The low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment was subjected to energy spectrum EDS analysis, and the results are shown in Table 2 below.

[0048] Table 2

[0049] element Mg Zr Zn O F Total Mass ratio (%) 10.85 40.66 19.27 27.97 1.25 100

[0050] As can be seen from Table 2, the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment is composed of elements such as Mg, Zr, Zn, O, and F.

[0051] The infrared emissivity, solar absorptivity and roughness tests were performed on the low-radiation absorption ratio white oxide ceramic coating in situ synthesized on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment. The test results showed that the infrared emissivity of the coating was 0.84, the solar absorptivity was 0.35, and the surface roughness was Ra5.89.

[0052] Figure 5 The surface scanning electron microscope image of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment is shown in FIG. Figure 5 It can be seen that the micropores of the coating have various sizes, which helps to adjust the thermal control performance of the coating.

[0053] Figure 6 The pore size distribution result of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment is shown in FIG. Figure 6 It can be seen that the pore size characteristics of the coating are: micropores with a pore size of less than 4μm account for 52%, micropores with a pore size of 4μm to 8μm account for 31%, micropores with a pore size of 8μm to 11μm account for 6%, and micropores with a pore size of 11μm to 18μm account for 11%.

[0054] Figure 7The cross-sectional scanning electron microscope image of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment is shown in FIG. Figure 7 It can be seen that the low radiation absorption ratio white oxide ceramic coating is tightly bonded to the LA103Z magnesium-lithium alloy substrate, indicating that the coating has excellent bonding strength.

[0055] Figure 8 The O1s binding energy diagram of the XPS analysis of the low radiation absorption ratio white oxide ceramic coating synthesized in situ on the surface of the LA103Z magnesium-lithium alloy sheet in this embodiment is shown in FIG. Figure 8 It can be seen that the main phases of the low radiation absorption ratio white oxide ceramic coating are ZrO2, ZnO and MgO.

[0056] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for in-situ synthesis of a low radiation absorption ratio white oxide ceramic coating on the surface of a magnesium-lithium alloy, characterized in that: The process of the method is as follows: a pre-treated LA103Z magnesium-lithium alloy is clamped by a hanger and placed in an electrolytic cell, and is completely immersed in an electrolyte and used as an anode, a stainless steel sheet is used as a cathode, and a power supply is set to a constant voltage segmented working mode for micro-arc oxidation treatment, and a low-radiation absorption ratio white oxide ceramic coating is in situ synthesized on the surface of the LA103Z magnesium-lithium alloy; the electrolyte is a zirconium salt-zinc salt system solution.

2. The method for in-situ synthesis of a low radiation absorption ratio white oxide ceramic coating on the surface of a magnesium-lithium alloy according to claim 1, characterized in that: The electrolyte comprises: ammonium fluorozirconate at a concentration of 6 g / L, sodium dihydrogen phosphate at a concentration of 6 g / L, ammonium fluoride at a concentration of 2 g / L, zinc dihydrogen phosphate at a concentration of 4 g / L to 16 g / L, and sodium hydroxide at a concentration of 1 g / L.

3. The method for in-situ synthesis of a low radiation absorption ratio white oxide ceramic coating on the surface of a magnesium-lithium alloy according to claim 1, characterized in that: The power supply is a constant voltage DC pulse power supply, and the process parameters of the micro-arc oxidation treatment are: end voltage 400V, frequency 1000Hz, duty cycle 15%, and oxidation time 15min.

4. The method for in-situ synthesis of a low radiation absorption ratio white oxide ceramic coating on the surface of a magnesium-lithium alloy according to claim 3, characterized in that: The voltage control method during the micro-arc oxidation treatment is segmented control, and the segmented control process is: in the initial stage of micro-arc oxidation, the voltage is increased from 0V to 300V during the period of 0 to 1min; During the 1-2 minute period of the micro-arc oxidation process, the voltage is increased from 300V to 350V; During the 2-5min period of the micro-arc oxidation process, the voltage is increased from 350V to 380V; During the 5-7min period of the micro-arc oxidation process, the voltage is increased from 380V to 400V; During the constant voltage stage of micro-arc oxidation, the voltage is maintained at 400V for 7min to 15min.

5. The method for in-situ synthesis of a low radiation absorption ratio white oxide ceramic coating on the surface of a magnesium-lithium alloy according to claim 1, characterized in that: The low radiation absorption ratio white oxide ceramic coating is mainly composed of ZrO2-ZnO-MgO, and the pore size characteristics of the coating are: micropores with a pore size below 4μm account for 52% to 74%, micropores with a pore size of 4μm to 8μm account for 23% to 31%, micropores with a pore size of 8μm to 11μm account for 2% to 6%, and micropores with a pore size of 11μm to 18μm account for 1% to 11%. The solar absorptivity of the coating is 0.35 to 0.56, the infrared emissivity of the coating is 0.79 to 0.84, and the surface roughness of the coating is Ra3.58 to Ra5.89.